2015
DOI: 10.56431/p-2tgz4p
|View full text |Cite
|
Sign up to set email alerts
|

Arrhenius Accelerated Life Test for Luminary Life of High Bright Light Emitting Diodes

Abstract: The High Bright Light Emitting Diodes (HBLEDs) generally having long life but very often its actual life is different from vendor’s specification. Vendors do not specify the failure criteria for their products but it may vary from 50% to 70% light output maintenance. Further time to test such a quantity takes too long under normal conditions. Longer time consumption for evaluation of such a quantity may not useful in mass production process of HBLEDs. The present study describes the determination of the useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As an example, Wang et al 173 reported a model in which the where A Tj and Ɵ are constants derived from a weighting of temperature and current-driven stress. Yang et al 172 reported an alternative model, developed for white LEDs, which again assumed junction temperature and drive current were the dominant factors, but used multiple-coupled stress ageing rather than constant stress conditions., i.e. different currents at the same temperature and different currents at different temperatures.…”
Section: Literature Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Wang et al 173 reported a model in which the where A Tj and Ɵ are constants derived from a weighting of temperature and current-driven stress. Yang et al 172 reported an alternative model, developed for white LEDs, which again assumed junction temperature and drive current were the dominant factors, but used multiple-coupled stress ageing rather than constant stress conditions., i.e. different currents at the same temperature and different currents at different temperatures.…”
Section: Literature Resultsmentioning
confidence: 99%
“…However, it does provide a reasonable fit to experimental data for white LEDs. 172 Zhang et al 48 made a quick assessment of the lifetime of transparent UV LEDs employing a p-AlN contact layer LED, through fitting of its EQE-J curves before and after short-term reliability test.…”
Section: N E Amentioning
confidence: 99%
“…The models proposed in this work can be used to model and predict long-term lumen maintenance (reliability) of LED arrays by using IES-LM-80 test data of single LEDs. Edirisinghe et al [161] used an Arrhenius accelerated life test model with the modeling parameter as the junction temperature in the determination of the useful lifetime of 1-W HBLEDs (high-bright light-emitting diodes). However, the proposed PoF models are too general, and they do not provide details about the various failure/degradation mechanisms for LEDs.…”
Section: Physics-based Methodsmentioning
confidence: 99%